La réglementation de l'intelligence artificielle dans le secteur de la conformité bancaire : approche européenne et canadienne - Gérard, Lorène (Université de Montréal, 2025)
Ce mémoire propose une analyse comparative de l'intégration de l'intelligence artificielle (IA) dans le secteur de la conformité bancaire, en s'intéressant aux approches européennes et canadiennes. Tandis que l'Union européenne a choisi de structurer cet encadrement à travers un règlement spécifique, le Canada avance de manière plus fragmentée, particulièrement depuis l'abandon du projet de loi C-27. Au fil de l'étude, plusieurs défis communs émergent : multiplication des normes, chevauchement des obligations, et insécurité juridique, autant de facteurs qui compliquent l'adoption d'outils d'IA dans le respect des exigences de conformité. L'analyse met en lumière les conséquences concrètes de cette fragmentation, notamment la hausse des coûts de conformité et un frein à l'innovation technologique. À partir de ces constats, ce travail propose des pistes pour clarifier et mieux articuler les règles existantes, en vue de bâtir un cadre plus lisible, cohérent et propice à l'innovation. En définitive, l’objectif poursuivi est d’esquisser les contours d’une régulation de l’IA adaptée aux défis du secteur bancaire, dans un contexte technologique en perpétuelle évolution. This thesis offers a comparative analysis of the integration of artificial intelligence (AI) into the field of banking compliance, focusing on the European and Canadian approaches. While the European Union has chosen to frame this integration through a specific regulation, Canada is advancing in a more fragmented manner, particularly following the abandonment of Bill C-27. Throughout the study, several common challenges emerge: the multiplication of standards, overlapping obligations, and legal uncertainty, all of which complicate the adoption of AI tools while ensuring regulatory compliance. The analysis highlights the concrete consequences of this fragmentation, including rising compliance costs and a potential slowdown in technological innovation. Based on these findings, this work proposes avenues for clarifying and better coordinating existing regulations, aiming to build a more coherent, understandable, and innovation-friendly framework. Ultimately, the goal is to outline a regulatory model for AI that meets the evolving challenges faced by the banking sector in an ever-changing technological landscape
Keywords: Artificial Intelligence; Banking Compliance; Cadre réglementaire canadien de l’IA; Cadre réglementaire européen de l’IA; Canadian Regulatory Framework for AI; Conformité bancaire; European regulatory framework for AI; Intelligence artificielle

La réglementation de l’intelligence artificielle dans le secteur de la conformité bancaire : approche européenne et canadienne - Gérard, Lorène (Université de Montréal, 2025)
Ce mémoire propose une analyse comparative de l'intégration de l'intelligence artificielle (IA) dans le secteur de la conformité bancaire, en s'intéressant aux approches européennes et canadiennes. Tandis que l'Union européenne a choisi de structurer cet encadrement à travers un règlement spécifique, le Canada avance de manière plus fragmentée, particulièrement depuis l'abandon du projet de loi C-27. Au fil de l'étude, plusieurs défis communs émergent : multiplication des normes, chevauchement des obligations, et insécurité juridique, autant de facteurs qui compliquent l'adoption d'outils d'IA dans le respect des exigences de conformité. L'analyse met en lumière les conséquences concrètes de cette fragmentation, notamment la hausse des coûts de conformité et un frein à l'innovation technologique. À partir de ces constats, ce travail propose des pistes pour clarifier et mieux articuler les règles existantes, en vue de bâtir un cadre plus lisible, cohérent et propice à l'innovation. En définitive, l’objectif poursuivi est d’esquisser les contours d’une régulation de l’IA adaptée aux défis du secteur bancaire, dans un contexte technologique en perpétuelle évolution. This thesis offers a comparative analysis of the integration of artificial intelligence (AI) into the field of banking compliance, focusing on the European and Canadian approaches. While the European Union has chosen to frame this integration through a specific regulation, Canada is advancing in a more fragmented manner, particularly following the abandonment of Bill C-27. Throughout the study, several common challenges emerge: the multiplication of standards, overlapping obligations, and legal uncertainty, all of which complicate the adoption of AI tools while ensuring regulatory compliance. The analysis highlights the concrete consequences of this fragmentation, including rising compliance costs and a potential slowdown in technological innovation. Based on these findings, this work proposes avenues for clarifying and better coordinating existing regulations, aiming to build a more coherent, understandable, and innovation-friendly framework. Ultimately, the goal is to outline a regulatory model for AI that meets the evolving challenges faced by the banking sector in an ever-changing technological landscape.
Keywords: AI; Artificial Intelligence; Banking Compliance; Cadre réglementaire canadien; Cadre réglementaire européen; Canadian Regulatory Framework; Conformité bancaire; European regulatory framework; IA; Intelligence artificielle

Le contrat intelligent, au secours du consommateur numérique - Mujangi, Mbombo (Université de Montréal, 2025)
Internet a révolutionné le commerce à distance en abolissant littéralement les barrières territoriales qui existaient entre le commerçant et le consommateur pour permettre des échanges dans un environnement dématérialisé. La pandémie de la Covid19 a été un tournant important pour le e-Commerce puisque le confinement qui s’en est suivi a presque obligé le monde à se tourner vers le virtuel qui a connu un boom spectaculaire. Presque tout se fait virtuellement au point que les épiceries aussi offrent la possibilité d’achat en ligne. Mais force est de constater que même dans le cyberespace, la relation entre le consommateur et le commerçant demeure déséquilibrée puisque ce-dernier reste celui qui édicte les règles du jeu. Dans ce travail, nous posons la question de savoir si les protections et garanties du consommateur, consacrées notamment par le Code Civil du Québec et la Loi sur la protection du consommateur, ont survécu avec le e-Commerce ou faut-il d’autres protections pour le consommateur dans le cyberespace? Nous postulons que le contrat intelligent peut être un moyen de sécuriser le consommateur dans le cadre du e-Commerce puisqu’il oblige le commerçant à clarifier les termes du contrat, offrant ainsi une prévisibilité de la relation contractuelle. Dans le cadre de notre travail, nous allons analyser les protections offertes actuellement au consommateur du commerce électronique en procédant à une analyse de droit comparé entre le Québec et la France dans le cadre de l’Union européenne. Puis nous verrons les avantages et inconvénients du contrat intelligent ce qui nous permettra de répondre à la question que nous posons à savoir s’il est un procédé salutaire qui remettrait l’équilibre dans la relation entre commerçant et le consommateur en assurant ainsi une protection adéquate à ce dernier. The Internet has revolutionized e-Commerce by literally abolishing the territorial barriers that existed between the merchant and the consumer to allow exchanges in a dematerialized environment. The Covid19 pandemic was an important turning point for e-Commerce since the subsequent lockdown almost forced the world to turn to the virtual, which experienced a spectacular boom. Almost everything is done virtually. Even grocery stores offer the possibility of online shopping. But even in cyberspace, the relationship between the consumer and the merchant remains unbalanced since the latter remains the one who dictates the rules of the game. In this work, we ask the question of whether consumer protections and guarantees, enshrined by the Quebec Civil Code and the Consumer Protection Act, have survived with e-Commerce or are there other consumer protections needed in cyberspace? We postulate that the smart contract can be a way to secure the consumer in the context of Ecommerce since it requires the merchant to clarify the terms of the contract. As part of our work, we will analyze the protections currently offered to consumers in electronic commerce by conducting a comparative law analysis between Quebec and France in the context of the European Union. Then we will see the advantages and disadvantages of the smart contract, which will allow us to answer the question whether it is a beneficial process that would restore balance in the relationship between merchant and consumer by ensuring adequate protection for the latter.
Keywords: Blockchain; Commerce électronique; Commerçant; Consommateur; Consumer; Consumer Protection Act; Consumer protection; Contrat en ligne; Contrat intelligent; Cyberespace; Cyberspace; Distance selling; Electronic commerce; Loi sur la protection du consommateur; Merchant; Online contract; Protection du consommateur; Smart contract; Vente à distance

Validité des clauses de non-concurrence et de non-sollicitation dans la vente d’entreprises au Québec : enjeux juridiques et particularités du secteur technologique et du commerce électronique - Costache, Leon Gabriel (Université de Montréal, 2025)
La validité des clauses de non-concurrence et de non-sollicitation dans les contrats d’achat d’actions ou d’actifs d’entreprise repose sur des critères précis établis par la jurisprudence, à savoir que les clauses restrictives doivent être limitées quant à leur durée, territoire et activités visées à ce qui est nécessaire pour protéger les intérêts légitimes de l’acheteur au moment de la transaction. Depuis l'arrêt Payette c. Guay, la jurisprudence a évolué pour offrir une plus grande flexibilité dans l’interprétation de ces clauses dans les contrats de vente d'entreprises, favorisant ainsi la liberté commerciale. Le rôle des tribunaux, dans l’évaluation de la validité de ces clauses et dans l’interprétation de leur portée, devient donc crucial, surtout en raison des lacunes législatives en la matière. Dans un contexte où les parties exercent leurs activités commerciales dans ou à l’aide du domaine technologique ou numérique, l’analyse des clauses doit tenir compte des réalités du marché, où l’évolution rapide des technologies et l’absence de limites géographiques remettent en question les présupposés traditionnels. Cependant, malgré cette évolution dans l’analyse des clauses de non-concurrence et de non-sollicitation, le cadre juridique actuel tend à privilégier presque exclusivement les intérêts privés des parties contractantes, au détriment de la considération de l’intérêt public. Cela soulève la question de savoir si cette approche, qui favorise la liberté contractuelle, ne devrait pas être rééquilibrée par une meilleure prise en compte des intérêts publics, tout en tenant compte des nouvelles réalités technologiques. The validity of non-compete and non-solicitation provisions in purchase of shares or assets agreements is based on specific criteria established by case law. Indeed, such restrictive covenants must be limited in terms of duration, territory, and activities covered to what is necessary to protect the legitimate interests of the buyer at the time of the transaction. Since the Payette v. Guay decision, case law has evolved to offer greater flexibility in the interpretation of these clauses in sale of business contracts, promoting commercial freedom. Thus, the role of the courts in assessing the validity of these restrictive provisions and interpreting their scope has become crucial, particularly due to the lack of legislative guidance. In contexts where the parties to such business transaction conduct their commercial activities in or with the help of technology, the analysis of the validity of non-compete and non-solicitation clauses must also take into account such new realities, where rapid technological advancements and the absence of geographical limits challenge traditional assumptions. However, despite recent evolutions in the analysis of non-compete and non-solicitation clauses, the current legal framework tends to almost exclusively prioritize the analysis of private interests of the contracting parties, at the expense of considering the public interest. This raises the question of whether this approach, which favors contractual freedom, should be rebalanced by a better consideration of public interests, while reflecting recent technological impacts.
Keywords: Business; Clause; Commercial; Competition law; Concurrence; Contract; Contrat; Digital; Entreprise; Non-compete; Non-concurrence; Non-solicitation; Non-sollicitation; Numérique; Technologie; Technology; Transaction

La contribution de la technologie vers une modernisation efficace des modes alternatifs de règlement de conflits - Sangare, Abou Bakary (Université de Montréal, 2025)
Les modes alternatifs de règlement de conflits ont révolutionné le monde du règlement de litiges grâce à leurs nombreux avantages. Les coûts moins onéreux en dehors de l’arbitrage, la célérité des procédures, la confidentialité, le dialogue ouvert, l’émergence de solutions créatives profitant plus ou moins à chacune des parties, constituent entre autres les nombreux éléments qui les rendent plus efficaces par rapport à une procédure contentieuse devant une instance judiciaire ordinaire. Cependant, ces modes alternatifs de règlement de conflits font quand même face à bien d’écueils qui les rendent au fil du temps moins efficaces. L’imprévisibilité des situations conflictuelles apportées à la table des instances de résolution, entraîne une inadéquation des solutions envisagées. De plus, le capital humain fait aussi défaut quand on sait que le nombre de ces règlements amiables de litiges de ces dernières années accroît considérablement, acculant ainsi le personnel de gestion de ces conflits qui se retrouve à faire face aux mêmes défis que le personnel des instances judiciaires contentieuses. De plus, l’humain ne pouvant se détacher indéfiniment de ses émotions peut très rapidement tomber dans la partialité quand il s’agit de prendre des décisions. Il est dès lors capital de penser à une modernisation de ces modes alternatifs de règlement de conflits afin de les rendre plus efficaces par le biais de nouveaux moyens technologiques. Certes, la Résolution de litiges en ligne existe depuis quelques années maintenant. Cependant, il est temps d’y apporter de nouveaux ingrédients afin de rendre meilleure la recette. Alternative dispute resolution has revolutionized the world of dispute resolution thanks to its many advantages. Lower costs, faster procedures, confidentiality, open dialogue and the emergence of creative solutions that benefit both parties to a greater or lesser extent - these are just some of the factors that make alternative dispute resolution more effective than litigation in the ordinary courts. However, these alternative dispute resolution methods do face a number of pitfalls that make them less effective over time. The unpredictability of conflict situations brought to the resolution table leads to inadequate solutions. What's more, human capital is also in short supply, as the number of out-of-court settlements in recent years has risen sharply, leaving conflict management staff facing the same challenges as staff in contentious legal proceedings. What's more, since human beings are unable to detach themselves from their emotions indefinitely, they can quickly fall into the trap of bias when it comes to making decisions. It is therefore vital to consider modernizing these alternative dispute resolution methods, in order to make them more effective through new technological means. Online dispute resolution has been around for some years now. However, it's time to add new ingredients to make the recipe even better.
Keywords: ADR; Alternative dispute resolution; Arbitrage; Arbitration; Blockchain; Chatbots; Conciliation; ICT; Internet; Justice; Justice prédictive; MARD; Mediation; Modes alternatifs de règlement de conflits; Médiation; Négociation; ODR; Online dispute resolution; Predictive justice; Règlement de litiges en ligne; TIC; Technologie; Technology; Transaction

A influência de terceiros sobre o controle societário interno: institutos, limites e regime de responsabilidade aplicável - uma análise necessária no âmbito da Lei n. 6.404/1976 - Silva, Ingrid Rodrigues da (Universidade de São Paulo, 2025)
Esta dissertação tem como objetivo analisar os limites jurídicos e o regime de responsabilidade aplicáveis à atuação de credores e demais terceiros alheios à estrutura societária que, direta ou indiretamente, influenciam o controle societário interno em deliberações societárias de sociedades por ações. Trata-se de uma temática ainda incipientemente explorada pela doutrina brasileira, o que impõe desafios teóricos relevantes e reforça a pertinência da investigação. A partir de uma abordagem fundamentada no ordenamento jurídico brasileiro, a pesquisa busca compreender de que modo agentes externos podem interferir no exercício do direito de voto e na condução das decisões estratégicas da companhia. A pesquisa desenvolveu-se inicialmente com a delimitação conceitual e histórica do direito de voto, examinando a dissociação entre a titularidade das ações e o efetivo exercício desse direito, a identificação do acionista controlador e as formas juridicamente reconhecidas de exercício do poder de controle. Na sequência, são analisados figuras ou institutos jurídicos que permitem a influência externa sobre o controle societário - como o penhor de ações, a alienação fiduciária em garantia, o usufruto, cláusulas de veto em geral e a figura do chamado "controle externo" - com ênfase nos efeitos decorrentes de consentimentos prévios ou autorizações concedidas por esses agentes em deliberações societárias. Diante da ausência de regulamentação específica sobre a atuação de credores ou terceiros no âmbito societário, bem como da não recepção, pelo ordenamento jurídico brasileiro, do controle externo como forma legítima de poder de controle, propõe-se uma construção doutrinária orientada à definição de limites objetivos para essa atuação. A proposta leva em consideração os riscos de conflito de interesses entre agentes externos, acionistas e a companhia e a análise da obrigatoriedade (ou não) de observância do interesse social por parte desses terceiros, no curso do processo de influência sobre os acionistas formalmente detentores do controle. Ao final, busca-se responder se o direito societário brasileiro oferece, ainda que de maneira indireta, mecanismos eficazes para coibir eventuais abusos na atuação de terceiros sobre o controle societário, e, em caso de violação, quais as consequências jurídicas e o regime de responsabilidade aplicável. This dissertation aims to analyze the legal boundaries and liability regime applicable to the conduct of creditors and other third parties external to the corporate structure who, directly or indirectly, influence internal corporate control in the decision-making processes of joint-stock companies. This topic remains incipiently addressed in Brazilian legal scholarship, which presents significant theoretical challenges and underscores the relevance of this investigation. Grounded in the Brazilian legal framework, the research seeks to understand how external agents may interfere with the exercise of voting rights and the formulation of strategic decisions within companies. The study begins with a conceptual and historical analysis of voting rights, examining the disassociation between share ownership and the actual exercise of voting power, the identification of the controlling shareholder, and the legally recognized forms of exercising corporate control. Subsequently, the dissertation examines legal mechanisms and arrangements that allow third-party influence over corporate control - such as share pledges, fiduciary transfers of shares in guarantee, usufruct rights, general veto clauses, and the so-called external control - with particular emphasis on the effects arising from prior consents or authorizations granted by these agents in corporate deliberations. Given the absence of specific regulation regarding the role of creditors or third parties in corporate governance, and considering that Brazilian law does not recognize external control as a legitimate form of exercising corporate power, this study proposes a doctrinal framework aimed at defining objective limits to such conduct. The proposal takes into account the risks of conflicts of interest among external agents, shareholders, and the company itself, as well as the analysis of whether these third parties must observe the corporate interest during the process of influencing shareholders who formally hold control. Finally, the dissertation seeks to determine whether Brazilian corporate law provides, even if indirectly, effective mechanisms to prevent abuses in third-party influence over corporate control and, in case of violations, what legal consequences and liability regimes are applicable.
Keywords: Controle societário; Corporate control; Creditors; Credores; Direito de voto; Influence over control; Influenciação sobre o controle; Legal limitations; Limites; Voting rights

Le droit de la concurrence et la protection des données personnelles sur la question d’abus de position dominante : affaire C-252/21 (Meta c. Bundeskartellamt) - Tang Manga, Marcelle Viviane (Université de Montréal, 2025)
L’affaire C-252/21 (Meta c. Bundeskartellamt) traite de la conformité du RGPD avec les pratiques commerciales de Meta et explore la question du rôle de la protection des données dans l’équilibre du jeu de la concurrence, notamment en matière d’abus de position dominante. Elle met d’abord en avant l’hypothèse selon laquelle la collecte et le traitement illicite de données pourraient constituer un facteur de verrouillage du marché à l’endroit des potentiels concurrents tout en renforçant la position dominante de Meta. Ensuite, elle conforte l’idée selon laquelle créer de la concurrence loyale entre les exploitants des données personnelles pourrait constituer un levier capable de renforcer la protection des données personnelles. Bien plus encore, on pourrait déduire de cette affaire un dualisme patent entre l'ultralibéralisme des marchés voulu par le système capitaliste américain, qui prend fait et cause pour le comportement prédateur de Méta, et la volonté protectrice de l’UE à travers son dispositif RGPD et ses politiques anticoncurrentielles. Il s’agira alors pour nous d’analyser l’impact du modèle économique de Meta sur le droit de la concurrence tout en s’interrogeant sur la capacité des outils réglementaires à répondre à la problématique d’abus de position dominante.
Keywords: Abus de position dominante; Abuse of dominant position; Collecte de données; Competencia; Competition law; Concurrence (droit); Consent; Consentement; Data collection; Personal information; Privacy; Publicité ciblée; Renseignements personnels; Targeted advertising; Vie privée

Les partenariats entre fintechs et banques à l’ère de l’intelligence artificielle : enjeux stratégiques et défis juridiques en droit des affaires - Awanvoeke, Larios Borgia Dona (Université de Montréal, 2025)
Les partenariats entre fintechs et banques à l’ère de l’intelligence artificielle redéfinissent les modèles économiques et stratégiques du secteur financier. Face aux mutations technologiques, les banques traditionnelles s’associent aux fintechs pour innover, optimiser leurs services et répondre aux attentes des consommateurs. Toutefois, ces collaborations soulèvent des défis juridiques majeurs en matière de responsabilité, de protection des données et de conformité réglementaire. Ce mémoire analyse ces enjeux en adoptant une méthodologie combinant analyse doctrinale, droit comparé et étude des cadres réglementaires existants. L’approche doctrinale a permis d’explorer les concepts clés des fintechs, des banques et de l’IA, en mobilisant les théories économiques et juridiques pertinentes. L’étude comparative entre l’Union européenne, les États-Unis et le Canada a mis en lumière les différences réglementaires, notamment en matière de protection des données et de régulation de l’innovation. Enfin, l’examen des cadres législatifs actuels et des tendances émergentes, telles que les regulatory sandboxes et les innovation hubs, a permis d’anticiper les évolutions nécessaires pour encadrer ces transformations. Les résultats montrent que si l’IA favorise l’innovation et l’automatisation des services financiers, elle pose également des risques en matière de transparence des algorithmes, de cybersécurité et d’équilibre concurrentiel. L’étude met en évidence la nécessité d’une harmonisation réglementaire et de mécanismes de gouvernance adaptés pour garantir un développement équilibré du secteur. Ce mémoire propose plusieurs recommandations, notamment le renforcement des cadres juridiques sur la responsabilité algorithmique, la création de normes internationales harmonisées et la mise en place de collaborations entre banques, fintechs et régulateurs. Ces mesures visent à assurer un environnement financier sécurisé, innovant et conforme aux impératifs de transparence et de protection des utilisateurs. Ainsi, les partenariats fintechs-banques s’imposent comme un levier stratégique incontournable, nécessitant une régulation adaptée pour concilier innovation et stabilité du marché.
Keywords: Algorithm Transparency; Algorithmic Liability; Artificial Intelligence; Automation; Automatisation; Banks; Banques; Business law; Cadre réglementaire; Comparative Law; Competencia; Competition; Concurrence; Cybersecurity; Cybersécurité; Data Protection; Digital Transformation; Droit comparé; Droit des affaires; Financial Governance; Financial Innovation; Fintechs; Gestion des risques; Gouvernance financière; Innovation Hubs; Innovation financière; Innovation hubs; Inteligência artificial; Intelligence Artificielle; Intelligence artificielle; Partenariats stratégiques; Protection des données; Regulatory Framework; Regulatory Sandboxes; Responsabilité algorithmique; Risk Management; Régulation; Régulatory sandboxes; Strategic Partnerships; Transformation numérique; Transparence des algorithmes

Le travail des enfants en Afrique subsaharienne et la responsabilité internationale des entreprises multinationales - Kouassi, Danielle-Esther Niangoran (Université de Montréal, 2025)
Les droits de l’enfant occupent aujourd’hui une place centrale dans le domaine des droits de la personne. De nombreuses conventions ont été adoptées pour protéger les enfants et leur reconnaître des droits spécifiques à leur condition. C’est ainsi que l’idée de l’interdiction du travail des enfants a été introduite, ce travail nuit à leur développement physique et mental ainsi qu’à leur éducation. Plusieurs organismes internationaux, comme l’Organisation des Nations Unies (ONU) et l’Organisation Internationale du Travail (OIT), se sont engagés à lutter contre ce phénomène. Cependant, en Afrique subsaharienne, cette lutte rencontre de nombreux obstacles et le travail des enfants y est encore monnaie courante. Face à cette situation, la communauté internationale (États, organismes internationaux, organisations non gouvernementales, etc.) a entrepris de nombreuses actions. Malheureusement, celles-ci ont une efficacité limitée en raison de l’absence d’implication d’acteurs primordiaux : les entreprises multinationales. Elles occupent une place de plus en plus importante sur la scène internationale et une partie de ces entreprises profite de l’exploitation des enfants dans les pays d’Afrique subsaharienne sans pour autant reconnaître ce phénomène ou leur implication directe ou indirecte. Aussi, l’état actuel du droit, plus précisément du droit international, rend difficile, voire impossible d’engager leur responsabilité. Ce travail de recherche va donc s’intéresser de plus près aux insuffisances des normes internationales adoptées et à la nécessité d’engager la responsabilité de ces entreprises du point de vue du droit international.
Keywords: Child labor; Children's rights; Conventions de l’OIT; Corporate Social Responsibility; Droits des enfants; Economic exploitation; Entreprises multinationales; Exploitation économique; Human rights violations; ILO conventions; International responsibility; Litiges transnationaux; Multinational corporations; Multinationales; Organisation international du travail; Responsabilité internationale; Transnational litigation; Travail des enfants; Violations des droits humains; international labor organization

Le sopravvenienze nei contratti di durata: tra risoluzione e adeguamento - Votta, Maria Luigia (LUISS Guido Carli, 2025)
La sopravvenienze nei contratti di durata. I contratti di durata–evoluzione della categoria. Le sopravvenienze contrattuali. La risoluzione come prodotto rimediale nei confronti delle sopravvenienze "tipiche". La risposta dell’ordinamento all’impossibilità sopravvenuta della prestazione–presupposti e disciplina. L’eccessiva onerosità sopravvenuta–ratio e presupposti applicativi. La rinegoziazione come strumento di adeguamento contrattuale. Il principio generale di adeguamento nei contratti di durata – il fenomeno dei relational contracts. La rinegoziazione come obbligo giuridico. Le clausole di adeguamento del contratto. La rinegoziazione di fonte pattizia. Le hardship clauses nel diritto internazionale. L’usura come sopravvenienza patologica–prospettive rimediali in un contesto interpretativo articolato. Recenti implicazioni dell'obbligo di rinegoziare. Il Covid-19 come sopravvenienza contrattuale–la normativa emergenziale. L’impatto del Covid-19 sulle locazioni commerciali. La rinegoziazione nel diritto della crisi d’impresa–luci e ombre nel nuovo impianto normativo. Il principio di rinegoziazione nel nuovo codice dei contratti pubblici.

The role of ADR and judicial agreements: legal analysis and behavioral economics insights - Solano Mantilla, Valeria (LUISS Guido Carli, 2025)
From rationality to reality. The evolution of law and economics through the behavioral lens. Understanding how we choose: foundations of behavioral economics. Rethinking law through the lens of behavioral economics. Why law needs behavioral economics. The challenge of integrating behavioral economics into private law: freedom vs regulation. The double-edged sword of behavioral economics: protecting consumers from psychological manipulation. Balancing innovation and consumer rights: a global view on consumer protection in the EU, Italy and Colombia. Alternative dispute resolution and the judicial agreements. The justice system seen though behavioral economics. Judicial agreements: procedural autonomy and enhancing judicial cooperation. Alternative dispute resolution (ADR) and mediation: legal frameworks, party autonomy and behavioral economic. A brief comparative analysis on mediation: EU, Italy and Colombia. Applying behavioral economics in the ADR (mediation).
Keywords: ADR; Alternative dispute resolution; Economic behaviour; Mediation; Médiation

L’exigence d’évaluation d’impact pour responsabiliser les entreprises face aux risques engendrés par l’intelligence artificielle - Pierre-Gilles, Cédrik (Université de Montréal, 2025)
La grande majorité des lois encadrant le développement ou le déploiement de systèmes d’intelligence artificielle (« IA ») à l’échelle mondiale impose aux acteurs privés de réaliser une forme d’évaluation d’impact. Ce type d’exigence vise à opérationnaliser un principe de responsabilité et plus précisément à instaurer une responsabilité ex ante destinée à prévenir les préjudices liés à l’IA, dans un contexte où la complexité et l’opacité de ces technologies entravent l’efficacité des mécanismes de responsabilité ex post. Lorsqu’on s’interroge sur la façon dont les exigences d’évaluation d’impact cherchent concrètement à responsabiliser les entreprises en amont, on constate qu’elles relèvent d’une approche de métarégulation : en incorporant ces exigences aux textes de loi, l’État mobilise les structures de régulation internes des entreprises afin que celles-ci gèrent par elles-mêmes les risques engendrés par l’IA. Les entreprises sont ainsi appelées à recueillir des données, à élaborer des normes, à modifier leurs pratiques – en somme, à réguler leurs propres activités – afin d’atténuer les effets indésirables que leurs projets relatifs à l’IA pourraient avoir sur la société, même lorsque ces effets demeurent incertains. Ainsi comprise, la démarche d’évaluation d’impact obligatoire contribue non seulement à une conduite dite responsable des entreprises, mais aussi à la conception d’une responsabilité juridique aux dimensions sociale et prospective.
Keywords: Artificial Intelligence; Autorégulation; Corporations; Entreprises; Gestion du risque; Impact assessment; Inteligência artificial; Intelligence Artificielle; Intelligence artificielle; Meta-regulation; Métarégulation; Responsabilité; Responsibility; Risk management; Évaluation d’impact

Le potentiel de la propriété intellectuelle pour le développement en Afrique : le cas du droit des marques dans les pays membres de l'OAPI - Massala, Kélicia (Université de Montréal, 2025)
Ce mémoire explore le potentiel du droit des marques comme levier stratégique de développement socio-économique dans les États membres de l’OAPI. En s’appuyant sur une analyse rigoureuse du système juridique harmonisé issu de l’Accord de Bangui, il met en lumière les forces et les limites du cadre actuel, à l’aune des défis structurels, institutionnels et économiques qui caractérisent la région. À travers une approche multidisciplinaire, combinant analyse doctrinale, données empiriques et entretiens de terrain, ce travail examine les mécanismes concrets de valorisation des marques locales, les disparités entre titulaires nationaux et étrangers, ainsi que les stratégies d’accompagnement en matière de sensibilisation, de formation et d’accès au système. Il propose également des pistes de réforme et des recommandations pour renforcer l’écosystème de la propriété intellectuelle au service de l’innovation, de la compétitivité des PME et de la protection des savoirs locaux. En filigrane, ce mémoire interroge la capacité des droits de propriété intellectuelle à contribuer de manière durable à l’émergence économique du continent africain.
Keywords: Développement économique; Economic Development; Innovation; Intellectual property; Legal Reforms; Marques; OAPI; PME; Propriedade intelectual; Propriété intellectuelle; Réformes juridiques; SMEs; Trademarks; Valorisation des savoirs locaux; Valorization of Local Knowledge

L'amélioration de l'accès à la justice au Bénin dans le domaine commercial et foncier : comment les modes alternatifs de règlement des conflits et la technologie peuvent être mis à contribution ? - Agoïnon, Fifamè Danielle Esperancia (Université de Montréal, 2025)
En dépit de l'importance cruciale de la justice au sein de notre société, il est manifeste que le système judiciaire béninois présente d'importants défis en matière d'accessibilité, d'efficacité et de confiance publique. Les coûts de la justice, la perte de contrôle des problèmes, les délais d’attente avant procès, la structure labyrinthique des tribunaux, l'impossibilité de se représenter seul, ainsi que le caractère inhospitalier des tribunaux constituent des indicateurs d'un système judiciaire défaillant. En effet, des limitations dans l'accès à la justice alimentent la méfiance des citoyens à l'égard du système judiciaire étatique. Dans un souci de célérité et d'efficacité de la justice, un vent de généralisation des modes alternatifs de règlement des conflits et de recours des technologies souffle sur les procédures judiciaires en général et sur les procédures civiles et commerciales en particulier. S’inscrivant dans cette logique, la loi n° 2020-08 du 23 Avril 2020 portant modernisation de la justice en République du Bénin n’a pas manqué de faire faire une place aux modes alternatifs de règlement des conflits. Elle met également un accent sur la dématérialisation progressive des procédures judiciaires concernant la saisine des juridictions, le suivi des procédures et le paiement électronique des frais afférents. Cependant, malgré ces mesures à encourager, les juridictions, au risque de rompre, ploient toujours devant les litiges fonciers et commerciaux. La présente étude a pour objet d'analyser les forces et les faiblesses du système judicaire béninois et vérifier si la modernisation des modes alternatifs de règlement des différends et l’intégration de la technologie dans les processus de résolution des différends peuvent être un vecteur de l’accès à la justice au Bénin. Despite the crucial importance of justice in our society, it is clear that the Beninese justice system presents significant challenges in terms of accessibility, efficiency and public trust. The costs of justice, the loss of control of problems, pre-trial waiting times, the labyrinthine structure of the courts, the inability to represent the costs of justice, the loss of control of problems, pre-trial waiting times, the labyrinthine structure of the courts, the inability to represent oneself, as well as the inhospitable nature of the courts are indicators of a broken justice system. Indeed, limitations in access to justice fuel citizens' mistrust of the state justice system. In the interests of speed and efficiency of justice, a wind of generalization of alternative methods of dispute resolution and recourse of technologies is blowing through judicial procedures in general and civil and commercial procedures in particular. In line with this logic, Law No. 2020-08 of 23 April 2020 on the modernization of justice in the Republic of Benin did not fail to make room for alternative methods of conflict resolution. It also emphasizes the gradual dematerialization of judicial procedures concerning the referral of cases to the courts, the monitoring of procedures and the electronic payment of related costs. However, despite these measures to be encouraged, the courts, at the risk of breaking down, are still bending before land and commercial disputes. The purpose of this study is to analyze the strengths and weaknesses of the Beninese judicial system and to verify whether the modernization of alternative dispute resolution methods and the integration of technology into dispute resolution processes can be a vector of access to justice in Benin.
Keywords: ACCESS TO JUSTICE; ADR; Accès à la justice; Business; Bénin; Commercial; Différend; Dispute; Foncier; Information; Land; MARD; Technologie; Technology

The regulation of crypto-assets in South Africa with particular regard to crypto-asset market manipulation - Mgijima, Lwandiso (University of Pretoria, 2025)
Market manipulation is one of the dishonest means used by unscrupulous investors to make unjustified profits. It is conduct which unlawfully interferes with the normal operations of the markets in order to create false appearances with respect to the trading activity or the price of a financial asset. Market abuse is one of the various challenges plaguing the crypto-assets market, and is one of the financial regulators’ priority concerns. This study examines and discusses the problem of market manipulation in crypto-assets, and the need for the enactment of an effective regulatory framework in order to combat this problem and to promote investor protection and safeguard the integrity of the markets. The study finds that South Africa and other countries need to introduce rules in crypto-assets market which aim at regulating the activities of crypto-asset service providers. Currently South Africa has not enacted a comprehensive regulatory framework to address the various illegal uses of crypto-assets. The general approach adopted by South Africa to regulate crypto-assets activities involves subjecting crypto-asset service providers and their activities under the various financial sector laws established to regulate the traditional financial markets. This approach has been criticised as being inefficient in light of the unique risks presented by crypto-assets. The study discusses some of these arguments in detail and concludes by highlighting the need for the adoption of innovative regulations, in the long term, which comprehensively and effectively addressed the various risks presented by crypto-assets which also include market manipulation.
Keywords: Crypto-asset; Crypto-assets; Framework; Manipulation; Markets; Misconduct; Regulation; Service provider

Cadre juridique du partenariat sino-camerounais : colonialité, investissement chinois et développement - Passi Soh, Babette Laurence (Université du Québec à Montréal, 2025)
Le travail de recherche aborde le cadre juridique du partenariat entre la Chine et le Cameroun, en se concentrant sur les impacts de la colonialité, des investissements chinois et du développement national. Le travail présente un sommaire structuré en plusieurs sections, chacune explorant divers aspects des relations sino-camerounaises.Dans la première section, le cadre juridique et politique de développement au Cameroun est examiné, mettant en lumière les influences historiques, notamment coloniales, sur le droit des affaires. Il est souligné que le Cameroun allie des systèmes juridiques de droit civil et de common law, hérités des périodes coloniales françaises et britanniques. Cette dualité rend difficile l’application uniforme des lois, ce qui se traduit par des inégalités dans les investissements étrangers, particulièrement ceux de la Chine, avec un cadre juridique isolé et sans harmonisation efficace présentant des défi s pour le développement économique. La politique de développement camerounaise, illustrée par la Stratégie Nationale de Développement (SND30) et la Vision 2035, vise à transformer l'économie. Les instruments juridiques entourant les partenariats publics-privés (PPP), comme les contrats de type Build-Operate-Transfer (BOT), sont analysés, mettant en avant les défi s d'une dépendance accrue vis-à-vis des financements chinois et des lacunes juridiques. La deuxième section traite du partenariat commercial avec la Chine, en se concentrant sur le Traité bilatéral d'investissement (TBI) et la présence croissante d'entreprises chinoises au Cameroun. Bien que ces investissements apportent des avantages, tels que la modernisation des infrastructures, ils soulèvent des préoccupations quant à la souveraineté économique et à un nouveau colonialisme économique. Le rapport souligne la nécessité d'un cadre normatif cohérent pour gérer les investissements afin d'entraîner une transformation économique durable. Les obstacles à l'atteinte des objectifs de la Vision 2035 sont également discutés, notamment l'incohérence du cadre normatif, la corruption et l'influence des élites. Le document préconise l'intégration de l'Afrikapitalisme, une idéologie économique axée sur le développement durable et inclusif, et suggère des réformes anti-corruption et l'adaptation des lois pour répondre aux besoins spécifiques du Cameroun. Enfin, la conclusion réaffirme l'importance de reconstruire un cadre juridique qui favorise une véritable coopération gagnant-gagnant avec les investisseurs étrangers, en tenant compte des réalités socio-économiques du pays. Le texte conclut en insistant sur la nécessité d'un équilibre entre les intérêts nationaux et l'attraction d'investissements, pour un développement durable et équitable.
Keywords: Afrique; Cameroun; Chine; Droit des affaires; Développement économique; Relations économiques extérieures

A cláusula de não concorrência : análise funcional e estrutural - Bedendi, Luís Felipe Ferrari (Universidade de São Paulo, 2025)
A dissertação propõe analisar a cláusula de não concorrência sob perspectivas funcional e estrutural, explorando suas origens históricas, fundamentos jurídicos e aplicações práticas, especialmente no contexto brasileiro. O estudo busca identificar os elementos essenciais dessa cláusula e avaliar sua compatibilidade com os princípios constitucionais da livre iniciativa e da concorrência, fundamentais à ordem econômica, além de posicioná-la perante o fenômeno da concorrência e o direito concorrencial. A pesquisa utiliza métodos históricos e dogmáticos, abrangendo análises legislativas, doutrinárias e jurisprudenciais. Também incorpora referências ao direito estrangeiro para examinar como a cláusula de não concorrência é tratada em diferentes sistemas jurídicos. A coleta de dados da jurisdição estatal e da atividade do Conselho Administrativo de Defesa Econômica permite compreender as interpretações dos órgãos decisórios brasileiros sobre a matéria. O estudo conclui que a cláusula de não concorrência desempenha um papel vital na proteção de investimentos e elementos imateriais, como clientela e segredos empresariais. Contudo, sua regulamentação no Brasil ainda é fragmentada, com previsões específicas no Código Civil, na Consolidação das Leis do Trabalho e na Lei de Franquias, sem que qualquer deles trate verdadeiramente do aspecto contratual da cláusula. Não obstante, conclui-se ser possível o encontro de elementos funcionais e estruturais comuns à cláusula, independentemente da relação jurídica base, a partir de que se propõe a categorizá-la como um instituto jurídico. Além disso, oferece subsídios para futuras discussões legislativas e jurisprudenciais, destacando a importância de conciliar a proteção de interesses econômicos com a promoção da livre concorrência. This dissertation analyzes the non-compete clause from functional and structural perspectives, exploring its historical origins, legal foundations, and practical applications, particularly in the Brazilian context. The study aims to identify the essential elements of this clause and evaluate its compatibility with the constitutional principles of free enterprise and competition, which are fundamental to the economic order, while positioning it in relation to the phenomenon of competition and antitrust law. The research employs historical and dogmatic methods, encompassing legislative, doctrinal, and jurisprudential analyses. References to foreign law are incorporated to examine how the non-compete clause is addressed in different legal systems. Data collected from state jurisdiction and the activities of the Administrative Council for Economic Defense provide insights into how Brazilian decision-making bodies interpret the matter. The study concludes that the non-compete clause plays a vital role in protecting investments and intangible elements such as clientele and trade secrets. However, its regulation in Brazil remains fragmented, with specific provisions in the Civil Code, the Consolidation of Labor Laws, and the Franchise Law, none of which adequately address the contractual aspect of the clause. Nevertheless, it is concluded that functional and structural elements common to the clause can be identified, regardless of the underlying legal relationship, leading to its proposed categorization as a legal institute. Furthermore, the dissertation offers resources for future legislative and jurisprudential discussions, emphasizing the importance of balancing the protection of economic interests with the promotion of free competition.
Keywords: Antitrust law; Cláusula de não concorrência; Direito concorrencial; Elementos estruturais; Funcionalidade; Functionality; Non-compete clause; Structural elements

La responsabilité civile sur les marchés financiers : les limites de la réglementation des valeurs mobilières quant à la protection des investisseurs en cas de pratiques abusives - Shab Afrouz, Shahrzad (Université de Montréal, 2025)
Ce mémoire étudie les limites de la réglementation des marchés financiers quant à la protection des investisseurs en cas de pratiques abusives et la responsabilité civile des défendeurs quant aux pertes économiques. Il compare les recours disponibles à l’investisseur prévu par le régime de responsabilité civile de la Loi sur les valeurs mobilières du Québec et le droit commun. Il établit l’importance de revoir les mécanismes de protection des investisseurs sur une base régulière pour assurer la stabilité des marchés financiers, tout en reconnaissant que la mise en œuvre de la réglementation des valeurs mobilières joue un rôle important dans la confiance du public sur les marchés financiers. Ce mémoire discute du défi auquel l’investisseur fait face quant au recouvrement des pertes attribuées à une faute commise sur les marchés financiers, particulièrement le défi de l’obtention de l’autorisation préalable du tribunal et de la preuve de causalité. Il faut reconnaitre que, pour établir un équilibre entre la protection des investisseurs et l’efficience des marchés, la coexistence du recours privé et public est nécessaire. Ces mesures ont pour objectif de décourager les pratiques déloyales sur les marchés financiers. De plus, l’étendue des dommages de l’investisseur doit être revue périodiquement et considérée à la lumière du contexte économique en cours pour assurer la cohérence du régime de responsabilité civile. En effet, il est important d’adopter une limite de responsabilité civile qui tient compte de l’aversion au risque de chacune des parties et qui ne désavantage pas l’une d’elles de manière excessive. Ceci permet d’atteindre un meilleur équilibre entre l’intérêt des investisseurs et les acteurs des marchés financiers, et de limiter le risque de poursuites opportunistes.
Keywords: Aversion au risques; Civil liability; Investissements; Investisseur (protection); Investments; Investor protection; Limites de responsabilité; Limits of liability; Marché financier; Protection des investisseurs; Responsabilité civile; Risk aversion; Valeurs mobilières

Climate justice and litigation in the context of South Africa - Chihombe, Denmark (North-West University, 2025)
This study interrogates the intersection of climate justice and litigation in the South African context. It addresses the urgent need for legal methods to address the disproportionate impact of climate change on marginalised communities. As climate change has become one of the greatest global challenges, marginalised communities most keenly feel its impacts, particularly those historically disadvantaged by socioeconomic inequalities rooted in apartheid. What follows is a critical examination of the most important international climate frameworks, in particular the United Nations Framework Convention on Climate Change (hereinafter UNFCCC) and the Paris Agreement, which have shaped the global discourse on climate change. The increasing recognition of the rights of historically marginalised and vulnerable communities underscores the potential role of climate litigation in achieving climate justice for all by holding both government and corporations accountable for their actions and lack thereof in mitigating climate change. The study examines the South African legal framework and recognises its progressive constitution that guarantees environmental rights. On the other hand, the study highlights significant barriers to effective climate action, particularly for the country’s most vulnerable, poor and marginalised populations, who often lack access to legal resources and skills needed for climate action. Using decided climate cases such as Earthlife Africa v. Minister of Environment, the study highlights the problems that plaintiffs often face when it comes to proving causation and the need for expert evidence in such litigation. Finally, the study concludes that while climate litigation offer opportunities for climate justice, the challenges identified need to be addressed to ensure the effectiveness of climate processes in achieving climate justice. The study therefore makes recommendations for strengthening legal aid, promoting public climate litigation and improving community capacity. By implementing these recommendations, climate justice will be achieved so that South Africa can effectively utilise climate litigation to demand climate justice for both current and future generations.
Keywords: Climate change; Global challenges; Justice; Litigation; Marginalised communities

A legal analysis of the application of the FATF grey-listing standards on South Africa - Mthembu, Zanele (North-West University, 2025)
The Financial Action Task Force (FATF) is a watchdog established to counter the abuse of the financial system by criminals for money laundering, the financing acts of terrorists and proliferation financing. For the FATF to achieve its mandate, it came up with a set of global standards in the form of Recommendations. The Recommendations seek to mitigate the risks of money laundering and terrorist financing and to assess whether FATF member countries are taking effective action to combat money laundering and terrorist financing. South Africa is a member of the FATF and therefore, is obliged to comply with the standards set to combat money laundering and terrorist financing and proliferation. The FATF uses assessments done through peer mutual evaluations. In other words, FATF members assess one another’s anti-money laundering and counter-terrorism financing (AML/CTF) regulatory frameworks for compliance with FATF’s standards. Following the FATF's assessment in the years 2003, 2009 and 2018, South Africa’s AML/CTF regulatory framework was found to be weak leading to greylisting in 2023. The greylisting of South Africa follows the findings of strategic deficiencies in the country’s implementation of the FATF AML/CFT standards. Greylisting by the FATF carries various economic and reputational implications for South Africa such as increased scrutiny from international partners resulting in increased compliance costs for financial institutions, an estimated reduction in South Africa’s gross domestic product (GDP) and a decrease in foreign direct investment (FDI). Since the greylisting, South Africa has embarked on a legislative and regulatory journey to address the shortcomings with a view to be taken off the greylist. This dissertation provides a detailed analysis of the FATF standards, evaluates South Africa's legislative and institutional responses in the form of the Prevention of Organised Crime Act 121 of 1998, Financial Intelligence Centre Act 38 of 2001 and the Protection of Constitutional Democracy Against Terrorist and Related Activities Act 33 of 2004, and assess their effectiveness in addressing the identified deficiencies. Recommendations are suggested to assist in fortifying South Africa’s AML/CTF regulatory framework.
Keywords: Accountable institutions; GAFI; Greylist; Money laundering; Mutual evaluation; Recommendations; Terrorism financing

The interpretation of social relations in the environmental, social and governance framework - Nxumalo, Nyiko (North-West University, 2025)
Environmental, social and governance (ESG) issues have gained prominence in recent years. Companies have come to understand their role in the global economy and that their decisions cannot be based solely on profits. They are now required to have regard for the environment in which they operate, to be mindful of the social factors that affect their employees, customers and the community at large, and to ensure that their corporate governance complies with the standards set out in the Companies Act 71 of 2008 and the various King Reports. While ESG has become a buzz word in the corporate world, there is still much uncertainty among stakeholders about what they are required to do and what the reporting requirements, if any, are. Its implementation in South Africa is still in its infancy and there is much uncertainty about what ESG monitoring and compliance truly entail. A perfect illustration of this is the fact that the Johannesburg Stock Exchange (JSE) only published ESG disclosure guidelines for the first time in 2022. This means that until the guidelines were published, hundreds of companies in South Africa had been wondering aimlessly in the dark when it comes to ESG issues. To make matters worse, while environmental issues and corporate governance issues have received significant attention from scholars and legislators in South Africa alike, the "S" in ESG has received little attention. It is often treated as the undesirable stepchild that everyone conveniently forgets is part of the ESG family. The purpose of this study is to highlight the gaps in the existing ESG regulatory framework, which leads to gaps in the understanding and monitoring of the implementation of the social indicators of ESG. The study aims to firstly determine whether companies in South Africa have a proper understanding of the social framework of ESG and whether the current legal and/or regulatory framework in South Africa offers sufficient guidance to n organisations to ensure that they comply with and fully implement the social guidelines of the ESG framework.
Keywords: ESG; ESG Framework; Governance factors; King IV report; Section 29 of Companies Act; Social factors; Social indicators

Expedited procedures in the Multilateral Investment Court: efficiency and consistency - Shouzab, Ali (Uppsala universitet, 2025)
The ongoing ISDS reform, under UNCITRAL Working Group III with a substantial input from the EU, has recently proposed for the establishment of a Multilateral Investment Court (MIC) with an appellate mechanism. Simultaneously, expedited arbitration procedures have gathered significant academic interest in the recent decades. While extensive literature exists on both the MIC development and expedited procedures, their intersection remains relatively unexplored. This dissertation bridges this research gap by analyzing how the best practices from different expedited procedures and EU treaties could be used to establish expedited MIC procedures. Adopting a doctrinal methodology, the research identifies the prominent models and trends in different expedited procedures, accesses their compatibility with the objectives of MIC, and finally proposes a suitable model to attain (cost and time) efficiency and consistency both for the first-tier and appellate proceedings in MIC. By doing so, the study contributes some recommendations for the development of expedited MIC procedures.
Keywords: Appellate Proceedings; Consistency; Efficiency; Expedited MIC Procedures; Expedited Procedures; First-Tier Proceedings; ISDS Reform; Multilateral Investment Court (MIC); UNCITRAL Working Group III

Anonim şirketin haklı sebeple feshinde haklı sebep teşkil edebilecek durumlar - Sunay Ece, Defne (Dokuz Eylül Üniversitesi, 2025)
6102 sayılı Türk Ticaret Kanunu m. 531'de anonim şirketin özel sona erme hallerinden biri olarak haklı sebeplerle fesih düzenlenmiştir. Bu düzenleme ile 6762 sayılı Türk Ticaret Kanunu döneminde anonim şirketin haklı sebeple feshinin mümkün olup olmadığı yönündeki tartışmalar sona ermiş ve anonim şirketin haklı sebeple feshi kurumu hukukumuza kazandırılmıştır. Anonim şirketin haklı sebeple feshi, haklı sebeplerin varlığı durumunda, sermayenin en az onda birini ve halka açık şirketlerde yirmide birini temsil eden pay sahipleri tarafından istenebilir. Anonim şirketin haklı sebeple feshi davası şirket merkezinin bulunduğu yer asliye ticaret mahkemesinde açılır. Kanunda anonim şirketin haklı sebeple feshinde haklı sebep kavramı tanımlanmamış ve haklı sebep teşkil edebilecek durumlara örnek gösterilmemiştir. Kanun gerekçesinde bu kavramın niteliklerinin gösterilmesinin ve tanımlanmasının yargı kararları ve doktrine bırakıldığı belirtilmiştir. İleri sürülen sebeplerin haklı sebep olarak kabul edilip edilmemesi mahkemenin takdirindedir. Yargılama sonucunda mahkemenin şirketin feshine, davacı pay sahiplerinin paylarının değerinin ödenerek şirketten çıkarılmasına veya uygun düşen ve kabul edilebilir diğer bir çözüme karar verme yetkisi bulunmaktadır. Çalışmamız kapsamında anonim şirketin haklı sebeple feshinde haklı sebep teşkil edebilecek durumlar incelenmiştir. Bu inceleme yapılırken kanun metni ve gerekçesi, doktrinde ileri sürülen görüşler ve yargı kararları ile çalışmamız desteklenmiştir. Article 531 of the Turkish Commercial Code No. 6102 regulates the dissolution of a joint stock company for just cause as one of its special grounds for termination. With the introduction of this provision, the debates regarding whether the dissolution of a joint stock company for just cause was possible under the period of the Turkish Commercial Code No. 6762 have been resolved, and the institution of dissolution of a joint stock company for just cause has been incorporated into our legal system. The dissolution of a joint stock company for just cause may be requested by shareholders representing at least one-tenth of the capital, or one-twentieth in publicly traded companies, in the presence of just causes. The lawsuit for the dissolution of a joint stock company for just cause is filed in the commercial court where the company's head office is located. The law does not define the concept of "just cause" in the context of the dissolution of a joint stock company, nor does it provide examples of situations that might constitute just cause. According to the legislative intent, the determination and definition of the characteristics of this concept are left to judicial decisions and legal doctrine. Whether the reasons presented are accepted as just cause is at the discretion of the court. Following the trial, the court has the authority to decide on the dissolution of the company, the payment of the value of the shares to the plaintiff shareholders in exchange for their exit from the company, or another suitable and acceptable solution. This study examines situations that may constitute just cause for the dissolution of a joint stock company for just cause. In this analysis, the text and rationale of the law, views expressed in legal doctrine and judicial decisions have been taken into account.
Keywords: Commercial Law; Corporate law; Dissolution; Joint Stock Company; Just Cause

Anonim şirketlerde imtiyazlı paylar ve imtiyazlı pay sahipleri özel kurulu - Tuğçe Altintaş, Fatma (Ufuk Üniversitesi, 2025)
Serbest piyasada önemli bir işleve sahip anonim şirketlerde, şirkete yeni sermaye sağlamak veya şirketteki mevcut pay sahiplerinin kontrolü elinde tutmak amacıyla imtiyazlı paylar oluşturulur. İmtiyazlı paylar (TTK m.478) ve imtiyazlı pay sahipleri özel kurulu (TTK m.454) ile şirketteki bazı paylara, diğer paylardan farklı ve üstün haklar, koruma mekanizmaları tanınmıştır. Bu çalışma kapsamında imtiyazlı paylar ve imtiyazlı pay sahipleri özel kurulu; 6102 sayılı Türk Ticaret Kanunu'ndaki (TTK) hükümler, mukayeseli hukuktaki düzenlemeler, öğreti görüşleri, Yargıtay kararları ve uygulamadaki sorunlar ele alınarak incelenmiştir. Konumuz ile ilgili tartışmalı hususlar, kanun ve yargı kararlarıyla netlik kazanması beklenen durumlar irdelenerek yeni bir bakış açısı kazandırmak amaçlanmıştır. Bu doğrultuda ''Anonim Şirketlerde İmtiyazlı Paylar ve İmtiyazlı Pay Sahipleri Özel Kurulu'' başlıklı tezimiz dört bölüm olarak hazırlanmıştır. ''İmtiyazlı Paylar'' başlıklı birinci bölümde, imtiyazlı pay kavramı, benzer kavramlar ve anonim şirketlere hakim olan ilkeler ile mukayese edilerek imtiyazlı pay ilkeleri çerçevesinde incelenmiştir. ''İmtiyazlı Pay Çeşitleri'' başlıklı ikinci bölümde, imtiyazlı pay çeşitleri incelenerek, bölümün ana omurgasını oluşturacak şekilde uygulamada en çok tartışılan hususlar olan, oy hakkında imtiyazlı paylar ve yönetim kurulunda temsil edilme hakkında imtiyazlı paylar irdelenmiştir. ''İmtiyazlı Pay Sahipleri Özel Kurulu'' başlıklı üçüncü bölümde imtiyazlı pay sahipleri özel kurulu kavramı, oluşturulma amacı, hukuki niteliği, mukayeseli hukukta imtiyazlı paylar ve imtiyazlı pay sahipleri özel kurulu, imtiyazlı pay sahipleri özel kurulunun toplanma şartları, toplanma süreci, toplanmasını gerektiren kararlar ve toplanmasına gerek olmayan durumlar ele alınarak incelenmiştir. ''İmtiyazlı Pay Sahipleri Özel Kurul Kararlarının Hukuki Etkisi, İptali ve Hükümsüzlüğü'' başlıklı dördüncü bölümde ise imtiyazlı pay sahipleri özel kurulu kararlarına karşı hukuki koruma mekanizmaları incelenmiştir. In joint-stock companies, which have an important function in the free market, privileged shares are created to provide new capital to the company or to maintain the control of the existing shareholders. In the Turkish Commercial Code No. 6102, privileged shares (TTK m. 478) and the special assembly of privileged shareholders (TTK m. 454) are regulated, granting certain shares in the company different and superior rights and protection mechanisms compared to other shares. With in the scope of this study, privileged shares and the special assembly of privileged shareholders have been examined by addressing the provisions of the Turkish Commercial Code No. 6102, comparative law regulations, doctrinal views, Supreme Court decisions, and practical issues. By examining the controversial issues related to our topic and the situations expected to gain clarity through laws and judicial decisions, it is aimed to provide a new perspective. In this context, our thesis titled "Special Shares and Special Shareholders in Joint-Stock Companies" has been prepared in four sections. In the first chapter titled "Preferred Shares," the concept of preferred shares was examined within the framework of preferred share principles by comparing it with similar concepts and the principles governing joint-stock companies. In the second section titled "Types of Preferred Shares," the various types of preferred shares are examined, focusing on the most debated issues in practice, namely, preferred shares with voting rights and preferred shares with representation on the board of directors, which form the main backbone of the section. In the third section titled "Special Assembly of Preferred Shareholders," the concept of the special assembly of preferred shareholders, its purpose of establishment, legal nature, preferred shares in comparative law, and the special assembly of preferred shareholders, the conditions for convening the special assembly of preferred shareholders, the process of convening, decisions requiring a meeting , and situations where a meeting is not necessary have been examined. In the fourth section titled "Legal Effect, Annulment, and Nullity of Preferred Shareholders Special Assembly Decisions," the legal protection mechanisms against the decisions of the preferred shareholders' special assembly are examined.